Plant polysaccharides influence tumor development based on epigenetics: a review - Li, Cong; Hu, Yuao; Yang, Hua (Frontiers in Pharmacology, 2025)
Plant polysaccharides have emerged as pivotal epigenetic modulators in oncology, offering multi-target therapeutic potential to address toxicity and drug resistance limitations of conventional therapies. This review integrates evidences from multi-database (PubMed, Web of Science and CNKI, 2010–2025) to elucidate three core epigenetic mechanisms of plant polysaccharides (e.g., Astragalus and Ganoderma lucidum): 1) TET2-mediated DNA demethylation; 2) inhibition of histone-modifying enzymes including JMJD2D; 3) regulation of tumor-suppressive miRNAs such as miR-139-5p. Preclinical studies demonstrate synergistic effects with chemotherapeutics, enhancing antitumor efficacy while reducing toxicity through immune modulation (e.g., H22 murine models) and organ protection (e.g., cisplatin regimens). Bibliometric analyses further uncover emerging roles in tumor microenvironment reprogramming, angiogenesis suppression, and macrophage polarization. These findings establish plant polysaccharides as precision oncology agents bridging molecular mechanisms with clinical translation. Future research should prioritize structural standardization, pharmacokinetic profiling, and combinatorial therapy optimization to accelerate clinical translation.